Unveiling hidden dangers: detecting undeclared toxic substances in refurbished vaporiser e-liquids - Shanwil Shaun Dsouza; Neha .; Palak Sharma; Sonal Jain (The Science of Nature, 2026)

Plant secondary metabolites: Integrating phytochemical characterization, in silico approaches, and biotechnological innovations for future applications - Priyanka; Pooja Sharma; Mahiti Gupta; Poonam Bansal; Raj Singh; Anil Kumar Sharma; Sonal Datta (Rhizosphere, 2026)

Triacylglycerols at the crossroads of lipid remodeling and stress tolerance in plants - Sonal Sharma; Vishal Varshney; Nishu Dhankhar; Kaberi Sonowal; Kritika Mehta; Ruchi Agarrwal; Kota Chakarpani; Pushpa Lohani; Vijay Gahlaut; Prafull Salvi (Plant Cell Reports, 2026)

Dopant-enabled diethylenetriamine penta(methylene phosphonic acid crosslinked polyaniline/polyvinyl alcohol hydrogel electrode for mechanically stable and high-rate flexible supercapacitor - Samaresh Ghosh; Sonal Sharma; Anasuya Bandyopadhyay (Chemical Engineering Journal, 2026)

Development of different regenerative modes for efficient propagation and phytochemical analysis in Tylophora indica (Burm. F.) Merrill: an important medicinal plant - Swati R. Patel; Ashutosh Pathak; Aruna Joshi; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Genetic polymorphisms of cytokine genes and their role in the susceptibility and severity of allergic fungal rhinosinusitis - Deeksha Chaudhary; Gargi Rai; Neelima Gupta; Sonal Sharma; Bineeta Kashyap; Praveen Kumar Singh; Sajad Ahmad Dar; Shukla Das (Archives of Microbiology, 2025)

The plant microbiome: A key driver of plant health and productivity - Aakriti Tiwari; Anil Kumar Sharma; Anil Kumar Pinnaka; Sonal Datta (Physiological and Molecular Plant Pathology, 2025)

Characterization and Application of Silicon Nanoparticles for Alleviation of Fluoride Stress in Avena sativa - Sonal Mishra; Nilima Kumari; Vinay Sharma (Journal of Soil Science and Plant Nutrition, 2025)

Co-liquefaction of sewage water grown Chlorella sorokiniana and Scenedesmus abundans for sustainable energy production - Sonal Vilas Shah; Bhawna Yadav Lamba; Avanish K. Tiwari; Rohit Sharma; Indra N. Pulidindi (Journal of Applied Phycology, 2025)

Mangrove phenological shifts over eco-climatic stressors in the Gulf of Kutch using Sentinel-1&2 time series data - Laxmi Kant Sharma; Sonal Sharma; Kariya Ishita Bhaveshkumar (Regional Studies in Marine Science, 2025)

Valorization of food waste stream by harnessing bioactive compounds: A comprehensive review on the process, challenges and solutions - Rachan Karmakar; Sonal Aggarwal; Deepika Kathuria; Narpinder Singh; Vijay Tripathi; Pradeep Kumar Sharma; Debasis Mitra; Sunil Kumar; Sourish Bhattacharya (Food Bioscience, 2025)

Circular economy in biohydrogen: A state-of-the-art review on advances in sustainable production, storage, and transportation - Amit Kumar Sharma; Praveen Kumar Ghodke; Wei-Hsin Chen; Sonal Vilas Shah; Alok Kumar Patel (Journal of Cleaner Production, 2025)

Shatavarin-IV rescues the Di (2-ethylhexyl) phthalate (DEHP) induced oxidative stress in rat granulosa cells in vitro - Vivek Pandey; Alka Sharma; Sonal Tiwari; Yashvant Patel; Jayhind Kumar Chauhan; Safiya Ayesha; Alakh N. Sahu; Rashmi Gupta; Anima Tripathi; Pawan K. Dubey (Reproductive Toxicology, 2024)

Molecular tools are crucial for malaria elimination - Himanshu Gupta; Sonal Sharma; Irina Gilyazova; Kapaettu Satyamoorthy (Molecular Biology Reports, 2024)

Enhancing Phosphate Uptake and Antifungal Activity in Tomato Plants via Bacillus licheniformis Mutagenesis: Evaluating Growth Parameters - Gaurav Kumar; Anjali Chauhan; Sonal Bhardwaj; Mohit Shukla; Shubham Sharma (Brazilian Journal of Microbiology, 2024)

Hydrogen peroxide mediated thermo-catalytic conversion of carbon dioxide to C1-C2 products over Cu (0) - Vishrant Kumar; Nicky Kumar Lamba; Aamir Baig; Amit Kumar Sonker; Nikhil Sharma; Jaidev Kaushik; Kumud Malika Tripathi; Sonal; Sumit Kumar Sonkar (Chemical Engineering Journal, 2024)

Development of microbial formulation to enhance the removal of high explosive octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) from contaminated soil - Ranju Sharma; Mohd. Aamir Khan; Sonal Yadav; Ngangbam Sarat Singh (Journal of Environmental Chemical Engineering, 2024)

Efficient oil spill cleanup from water: Investigating the effectiveness of a sustainable anti-swelling hydrogel for rapid water repellency and oil absorption - Sonal Choudhary; Kashma Sharma; Vijay Kumar; Vishal Sharma (Chemosphere, 2024)

Tissue Engineered 3D Constructs for Volumetric Muscle Loss - Sonal Gahlawat; Doga Oruc; Nikhil Paul; Mark Ragheb; Swati Patel; Oyinkansola Fasasi; Peeyush Sharma; David I. Shreiber; Joseph W. Freeman (Annals of Biomedical Engineering, 2024)
Severe injuries to skeletal muscles, including cases of volumetric muscle loss (VML), are linked to substantial tissue damage, resulting in functional impairment and lasting disability. While skeletal muscle can regenerate following minor damage, extensive tissue loss in VML disrupts the natural regenerative capacity of the affected muscle tissue. Existing clinical approaches for VML, such as soft-tissue reconstruction and advanced bracing methods, need to be revised to restore tissue function and are associated with limitations in tissue availability and donor-site complications. Advancements in tissue engineering (TE), particularly in scaffold design and the delivery of cells and growth factors, show promising potential for regenerating damaged skeletal muscle tissue and restoring function. This article provides a brief overview of the pathophysiology of VML and critiques the shortcomings of current treatments. The subsequent section focuses on the criteria for designing TE scaffolds, offering insights into various natural and synthetic biomaterials and cell types for effectively regenerating skeletal muscle. We also review multiple TE strategies involving both acellular and cellular scaffolds to encourage the development and maturation of muscle tissue and facilitate integration, vascularization, and innervation. Finally, the article explores technical challenges hindering successful translation into clinical applications.

Ultra-sensitive detection and scavenging of arsenic ions and ciprofloxacin using 3D multipurpose hemicellulose based aerogel: Adsorption mechanism and RSM optimization - Kavita Sharma; Manpreet Kaur; Preeti Tewatia; Vijay Kumar; Christian Paulik; Hideaki Yoshitake; Mukta Sharma; Gaurav Rattan; Sonal Singhal; Anupama Kaushik (Bioresource Technology, 2023)

Comprehensive analysis using DNA metabarcoding, SCAR marker based PCR assay, and HPLC unveils the adulteration in Brahmi herbal products - Abhi P. Shah; Tasnim Travadi; Sonal Sharma; Ramesh Pandit; Chaitanya Joshi; Madhvi Joshi (Molecular Biology Reports, 2023)

Development of Thermotolerant Lactobacilli Cultures with Improved Probiotic Properties Using Adaptive Laboratory Evolution Method - Jyothna Bommasamudram; Pradeep Kumar; Sonal Kapur; Deepak Sharma; Somashekar Devappa (Probiotics and Antimicrobial Proteins, 2023)

Potentially toxic metals contamination, health risk, and source apportionment in the agricultural soils around industrial areas, Firozabad, Uttar Pradesh, India: a multivariate statistical approach - Anuj Saraswat; Shri Ram; Md Basit Raza; Sadikul Islam; Sonal Sharma; Michael E. Omeka; Biswaranjan Behera; Roomesh K. Jena; Abdur Rashid; Debasis Golui (Environmental Monitoring and Assessment, 2023)

Elicitor mediated enhancement of shoot biomass and lupeol production in Hemidesmus indicus (L.) R. Br. ex. Schult. and Tylophora indica (Burm. F.) Merrill using yeast extract and salicylic acid - Ashutosh R. Pathak; Swati R. Patel; Aruna G. Joshi; Neeta Shrivastava; Gaurang Sindhav; Sonal Sharma; Hafsa Ansari (Natural Product Research, 2023)

Bioremediation of multifarious pollutants using laccase immobilized on magnetized and carbonyldiimidazole-functionalized cellulose nanofibers - Kavita Sharma; Preeti Tewatia; Manpreet Kaur; Deepak Pathania; Fawzi Banat; Gaurav Rattan; Sonal Singhal; Anupama Kaushik (Science of The Total Environment, 2023)

Insight into Exopolysaccharide-Mediated Stress Tolerance in Plants: a Feasible Approach Towards the Development of Next-Generation Bioformulations - Sonal Srivastava; Shilpi Sharma (Journal of Soil Science and Plant Nutrition, 2023)

Biosynthesis of nanostructured silver by green algae and evaluation of its microbicidal property against pathogenic microbes - Sonal Dixit; Neha Vishnoi; Neha Mani Tripathi; D. P. Singh; Yogesh Kumar Sharma (Environmental Sustainability, 2022)

Safety assessment of the pharmacological excipient, diethylene glycol monoethyl ether (DEGEE), using in vitro and in vivo systems - Sonal Srivastava; Sakshi Mishra; Jayant Dewangan; Aman Divakar; Nidhi Gupta; Navodayam Kalleti; Madhav Nilakanth Mugale; Sadan Kumar; Sharad Sharma; Srikanta Kumar Rath (DARU Journal of Pharmaceutical Sciences, 2022)

The multifaceted role of mangiferin in health and diseases: a review - Ashok Jangra; Mandeep Kumar Arora; Anglina Kisku; Sonal Sharma (Advances in Traditional Medicine, 2021)

Somatic embryogenesis in Leptadenia reticulata (Retz.) Wight and Arn along with assessment of shoot and callus cultures for HPTLC fingerprint and quantification of p-coumaric acid - Swati R. Patel; Aruna G. Joshi; Ashutosh R. Pathak; Neeta Shrivastava; Sonal Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Chemical Profiling of Tylophora indica (Burm. F.) Merrill. Shoot Cultures Established Through Leaf Explant - Swati R. Patel; Ashutosh R. Pathak; Aruna G. Joshi; Neeta Shrivastava; Sonal Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Development and Characterization of Biocompatible Mannose Functionalized Mesospheres: an Effective Chemotherapeutic Approach for Lung Cancer Targeting - Laxmikant Gautam; Rajeev Sharma; Priya Shrivastava; Sonal Vyas; S. P. Vyas (AAPS PharmSciTech, 2020)

Safety assessment of the pharmacological excipient, diethylene glycol monoethyl ether (DEGEE), using in vitro and in vivo systems - Sonal Srivastava; Sakshi Mishra; Jayant Dewangan; Aman Divakar; Nidhi Gupta; Navodayam Kalleti; Madhav Nilakanth Mugale; Sadan Kumar; Sharad Sharma; Srikanta Kumar Rath (DARU Journal of Pharmaceutical Sciences, 2019)

Obliteration of phosphorus deficiency in plants by microbial interceded approach - Bhawna Dipta; Sonal Bhardwaj; Manoj Kaushal; Shruti Kirti; Ruchi Sharma (Symbiosis, 2019)

Activation of endoplasmic reticulum stress in rat brain following low-intensity microwave exposure - Ranjeet Kumar; Pravin S. Deshmukh; Sonal Sharma; BasuDev Banerjee (Environmental Science and Pollution Research, 2019)

Lipid-Based Nanocarriers for Lymphatic Transportation - Nikhar Vishwakarma; Anamika Jain; Rajeev Sharma; Nishi Mody; Sonal Vyas; Suresh P. Vyas (AAPS PharmSciTech, 2019)

Nanocarrier-Based Combination Chemotherapy for Resistant Tumor: Development, Characterization, and Ex Vivo Cytotoxicity Assessment - Sarjana Raikwar; Sonal Vyas; Rajeev Sharma; Nishi Mody; Surbhi Dubey; Suresh P. Vyas (AAPS PharmSciTech, 2018)

Intravaginal Delivery of Polyphenon 60 and Curcumin Nanoemulsion Gel - Atinderpal Kaur; Yashaswee Saxena; Rakhi Bansal; Sonal Gupta; Amit Tyagi; Rakesh Kumar Sharma; Javed Ali; Amulya Kumar Panda; Reema Gabrani; Shweta Dang (AAPS PharmSciTech, 2017)

Homogenous PCR of Heterogeneous DNA from Phenolic Rich Barks of Terminalia Species for DNA Based Adulteration Detection - Sonal Sharma; Poojadevi Sharma; Sheetal Yadav; Indira Purohit; Anshu Srivastava; Astha Varma; Neeta Shrivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Renaissance in phytomedicines: promising implications of NGS technologies - Sonal Sharma; Neeta Shrivastava (Planta, 2016)